Source parameters of the M 6.5 Skyros Island (North Aegean Sea) earthquake of July 26, 2001 - A. Kiratzi; Z. Roumelioti; C. Benetatos; N. Melis (Annals of Geophysics, 2002)
Teleseismic body wave modelling, time domain moment tensor inversion of regional waveforms and spectral analysis of the far-field P-wave pulses are used to derive the source parameters of the July 26, 2001 Skyros earthquake (M 6.5). Its epicentre is located south of the Sporades Islands in the North Aegean Sea (Greece). Previous focal mechanism solutions indicate motion on strike-slip faults. The time domain moment tensor inversion is applied for the first time to the regional waveforms of the recently established broadband network in Greece. Its application gave results which are highly consistent with teleseismic waveform modelling. The results of this study, in combination with the distribution of aftershocks, indicate left-lateral strike slip motion on a NW-SE striking fault with parameters: fault plane (strike = 151°, dip = 83°, rake = 7°) and auxiliary plane (strike = 60°, dip = 84°, rake = 173°), depth 12 km and M 0 = 5.98e18 N m. Moreover, the time domain moment tensor inversion technique yielded a pure double couple source with negligible CLVD. The spectral analysis of the far-field P-wave pulses resulted in a fault length L ~ 32 km, stress drop ~ 9 bars and average displacement u ~ 30 cm.These values are in very good agreement with those estimated from empirical scaling relations applicable to the Aegean area.